A Behavioral Analysis of Spatial Neglect and its Recovery After Stroke - Rengachary, Jennifer; He, Biyu J.; Shulman, Gordon; Corbetta, Maurizio (Frontiers in Human Neuroscience, 2011)
In a longitudinal study of recovery of left neglect following stroke using reaction time computerized assessment, we find that lateralized spatial deficits of attention and perception to be more severe than disturbance of action. Perceptual-attention deficits also show the most variability in the course of recovery, making them prime candidates for intervention. In an anatomical analysis of MRI findings, ventral frontal cortex damage was correlated with the most severe neglect, reflecting impaired fronto-parietal communication.